Pharmacokinetic Properties of Acetyl Tributyl Citrate, a Pharmaceutical Excipient - Hyeon Kim; Min Sun Choi; Young Seok Ji; In Sook Kim; Gi Beom Kim; In Yong Bae; Myung Chan Gye; Hye Hyun Yoo (MDPI AG, 2018)
Acetyl tributyl citrate (ATBC) is an (the Food and Drug Administration) FDA-approved substance for use as a pharmaceutical excipient. It is used in pharmaceutical coating of solid oral dosage forms such as coated tablets or capsules. However, the information of ATBC on its pharmacokinetics is limited. The aim of this study is to investigate the pharmacokinetic properties of ATBC using liquid chromatography–tandem mass spectrometric (LC–MS/MS) analysis. ATBC was rapidly absorbed and eliminated and the bioavailability was 27.4% in rats. The results of metabolic stability tests revealed that metabolic clearance may have accounted for a considerable portion of the total clearance of ATBC. These pharmacokinetic data would be useful in studies investigating the safety and toxicity of ATBC.